Company tax coordination cum tax rate competition in the European Union - Wolfgang Eggert; Andreas Haufler (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2006)
This paper reviews the recent theoretical literature that analyses the European Union's policy to eliminate preferential corporate tax regimes and the proposal to introduce a consolidated EU tax base with formula apportionment for the taxation of multinational firms. Since neither proposal includes a harmonisation of corporate tax rates, a core issue is how tax competition between member states will be affected by these partial coordination measures. The conclusions from our review are supportive of the EU's ban on preferential tax regimes, but the economic incentive effects of a switch to formula apportionment are found to be ambiguous.
urn:nbn:de:bvb:19-epub-902-8
Keywords: H25; F23; H87; 330; corporate taxation; tax coordination; multinational firms; Unternehmensbesteuerung; Steuerbelastung; Multinationales Unternehmen; Steuerwettbewerb; EU-Steuerrecht; EU-Staaten